2018
DOI: 10.7897/2230-8407.097127
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pharmacist's Role in Counselling and Educating Diabetic Patients About Insulin Therapy

Abstract: Background: Insulin therapy is the cornerstone treatment for diabetic patients. Insulin administration errors are common and may pose a significant risk to the life of the patient. Pharmacists can play an important role in educating and counseling diabetic patients about the proper use of insulin to prevent such errors. Objective: to evaluate the role of community pharmacists in educating diabetic patients about the proper use of insulin. Setting: This study was conducted on a convenient sample of 54 pharmacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…The target populations in all the studies were CP 28 (62.2%), 19-Boura F, Al-Tabakha M, Hassan N, Darwich M. Critical appraisal of simulated patient methodology to assess the practice of community pharmacist in the Middle East and North Africa region: A systematic review. Pharmacy Practice 2022 Jul-Sep;20(3):2701. https://doi.org/10.18549/PharmPract.2022.3.2701 3 22,24,26,29,30,[32][33][34][35]38,39,41,42,46,47,[49][50][51][52][53][54][55][58][59][60] pharmacy staff (pharmacists and non-pharmacists) 10 (22.2%), 18,23,31,36,37,43,44,48,57,60 and CP and GP 1 (2.2%). 27 Table 1 provides a summary of the descriptive characteristics of the included studies in the review.…”
Section: The Characteristics Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The target populations in all the studies were CP 28 (62.2%), 19-Boura F, Al-Tabakha M, Hassan N, Darwich M. Critical appraisal of simulated patient methodology to assess the practice of community pharmacist in the Middle East and North Africa region: A systematic review. Pharmacy Practice 2022 Jul-Sep;20(3):2701. https://doi.org/10.18549/PharmPract.2022.3.2701 3 22,24,26,29,30,[32][33][34][35]38,39,41,42,46,47,[49][50][51][52][53][54][55][58][59][60] pharmacy staff (pharmacists and non-pharmacists) 10 (22.2%), 18,23,31,36,37,43,44,48,57,60 and CP and GP 1 (2.2%). 27 Table 1 provides a summary of the descriptive characteristics of the included studies in the review.…”
Section: The Characteristics Of the Included Studiesmentioning
confidence: 99%
“…22,30,35,46 In addition, some studies reported the counseling/dispensing duration 14 (31.1%), 26,28,31,35,36,[41][42][43]45,48,50,52,56,58 visit duration 7 (15.6%), 19,29,42,52,[60][61][62] and/or waiting duration 3 (6.7%). 22,36,52 The most outcome measured in the included studies was the adequacy of skill (pre-dispensing and/or post-dispensing) 38 (84.4%), 19,21,22,[24][25][26][27][28][29][30][31][32][33][34][35][36]38,[40][41][42][43][44]…”
Section: The Outcomes Measures and Major Findings Of The Included Stu...mentioning
confidence: 99%
See 3 more Smart Citations